Acute consumption of an energy drink does not improve physical performance of female volleyball players - Fernandez-Campos, C.; Dengo, A. L.; Moncada-Jimenez, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
To determine the acute effect of an energy drink (ED) on physical performance of professional female volleyball players. 19 females (age= 22.3 ± 4.9 yr.; height= 171.8 ± 9.4 cm; weight= 65.2 ± 10.1 kg) participated in a randomized, crossover, double-blind study to measure grip strength, vertical jump and anaerobic power in 3 different sessions (ED, placebo [PL] or no beverage [CTL]). For each session, participants arrived in a fasted state, consumed a standardized breakfast meal, and 1 hr later completed the 3 baseline performance tests without having ingested the beverage. After completing the premeasurements, the athletes drank 6 ml/kg of body weight of the ED or PL and in the CTL condition no beverage was consumed. Posttest measurements were taken 30 min after the ingestion of liquids. A 3 × 2 repeated-measures ANOVA revealed no significant within-session and measurement time interactions for each performance test. Regardless of the measurement time, right hand grip strength was significantly higher in the ED condition (34.6 ± 0.9 kg) compared with PL (33.4 ± 1.1 kg) and CTL (33.6 ± 1.0 kg) (p < .05). Regardless of the beverage ingested, averaged right hand grip strength, taking into account all 3 testing conditions, increased from pre to posttesting (Pre = 33.8 ± 0.9 kg vs. Post = 33.9 ± 1.0 kg; p = .029), as did the averaged fatigue index, obtained from the anaerobic power test (Pre = 65.9± 2.2% vs. Post = 68.7± 2.0%; p= .049). The acute ingestion of an ED did not improve physical performance of professional Costa Rican female volleyball players.